Creating Competitive Advantages for Business Trade Entrepreneurs in Luang Prabang city, Luang Prabang Province - Layaseng, Somyot; Silivong, Phonevilay; Sifongxay, Sangthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research study aims to examine the competitive situation of business trade operators and to study the creation of competitive advantages of business trade operators in Luang Prabang Municipality, Luang Prabang Province, using quantitative questionnaires to collecting data from a sample group of 170 business trade operators in Luang Prabang Municipality, and the statistics used in the analysis are frequency, percentage, mean, and standard deviation. The findings revealed that the competitive situation of business trade entrepreneurs in Luang Prabang city, Luang Prabang Province, according to industry competition, was found to have high-level pressure, which comes from: the pressure of current business trade competitors in terms of their ability to manage business trade operations with the most cost-effective unit cost compared to competitors; the pressure of entry by new competitors in terms of product costs and business management costs being so low that new competitors cannot achieve them; the pressure from the bargaining power of suppliers/raw material providers in terms of the ability to source products/raw materials from other sources with lower costs; the pressure from the bargaining power of buyers in terms of customers being unable to find substitute products due to differences in price and quality; and the pressure from the bargaining power of substitute products in terms of the ability to adapt strategies in seeking new product formats to meet consumer demands. The creation of competitive advantages of business entrepreneurs in Luang Prabang city, Luang Prabang Province was found to be at a high level, which comes from: differentiation in terms of businesses introducing new product models that differ from competitors to the market and creating customer impressions; rapid response in terms of the ability to introduce new products and respond quickly to customer demands; relationship activities in terms of maintaining good and close relationships with customers to immediately respond to changing customer needs; and cost leadership in terms of the ability to reduce operational costs by using available resources efficiently.